(untitled) (Bangladesh Journal of Zoology, 2025)
This article studies the histopathological effects of paper mill effluent on the testes of the freshwater fish, Rasbora daniconius. In this experiment, freshwater fish, Rasbora daniconius, were exposed to lethal concentrations of 9.5% (96-hour LC50) for 96 hours and sublethal concentrations [1.9% (1/ 5) and 0.95% (1/10) 96-hour LC50] for 30 days. A second group of fish without exposure to paper mill effluent was treated as a control. Control testes appeared structurally normal. Fish testes exposed to a 96-hour lethal concentration of 9.5% (LC50) paper mill effluent showed apparent degeneration of lobules, necrosis and vacuolation of the testicular lumen and connective tissues. At a concentration of 0.95% paper mill effluent for 30 days of exposure, significant changes were observed in the seminiferous tubules: necrosis and vacuolated testicular lumen, disruption of tubule boundaries, cellular hypertrophy and absorption of spermatozoa. After exposure to a concentration of 1.9% of paper mill effluent for 30 days, distinct lesions appear such as rupture of tubule boundaries and liquefaction at the spermatogonium stage with blood hemorrhage in several locations. Complete sperm absorption with cellular vacuolation was also observed. The interstitial cells were found to disintegrate. Bangladesh J. Zool. 52(3): 301-309, 2024